The principle of Ma Yozman in Iranian Civil Law: a Comparative Study - Hamzh Asfandiyari; Mahsa Madani (پژوهش تطبیقی حقوق اسلام و غرب, 2015)
The Ma Yozman principle (ما یضمن) is one very famous principle in the Islamic jurisprudence. Though it does not have any grounding in Islamic traditions, it has been widely established as a principle in Islamic traditions and some other principles taken from Islamic legal texts. This principle has two parts: the original principle and its reverse order. The principle states that if a contract is applicable, then the opposite of it is also applicable, and if a contract is inapplicable, then the opposite of it is also inapplicable. One can find traces of the contents of this principle in the Iranian Civil Law. However, there are opposing views as some lawyers basically consider it to be void. In the present article, we make an attempt to study the application of this principle in the civil law. In so doing we have a comparative study of Shia Jurisprudence and the general Islamic Jurisprudence. We also address some relevant topics in French Law.